PENGARUH PERHATIAN ORANG TUA DAN PERGAULAN TEMAN SEBAYA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS X DI SMK GEMA NUSANTARA BUKITTINGGI - Gifra, gifra; Yulia Rahman (IAIN Ambon, 2024)
This research was motivated by the existence of a striking gap in PAI learning outcomes scores between students who had good parental attention and good peer relationships and students who had less good attention and peer relationships. Based on this background, researchers are interested in conducting research on the influence of parental attention and peer interaction on student learning outcomes in PAI subjects. The purpose of this research is to determine the influence of parental attention on PAI learning outcomes, to determine the influence of peer interaction on PAI learning outcomes, to determine the significance of the influence of parental attention and peer interaction on PAI learning outcomes. The hypothesis of this research is that there is an influence of parental attention and peer interaction on PAI learning outcomes. This type of research is quantitative using correlation (questionnaire). The population in this research is 49 class X students at SMK Gema Nusantara Bukittinggi. The results of this research are that there is a significant influence of parental attention and peer interaction on student learning outcomes in class X PAI subjects at Gema Nusantara Vocational School, Bukittinggi.